Analisis emisi gas buang dan daya sepeda motor pada volume silinder diperkecil - I.M. Mara; I.M.A. Sayoga; I.G.N.K. Yudhyadi; I.M. Nuarsa (Universitas Mataram, 2018)
This research aims to determine the effect of variations diameter pistons on exhaust emissions and fuel consumption. This research used a gasoline engine single-cylinder four-stroke with variations in cylinder volume 100 cc, 90 cc, 60 cc and engine rotation 1500 rpm, 2500 rpm, 3500 rpm, 4500 rpm, 6000 rpm. Data was collected in transmission N, 1, 2, 3, and 4 each of the three repetitions for each round engine rotation, using a gas analyzer 2400 ultra 4/5 IM Hanatech brand for exhaust emission of CO and HC. Based on data analysis, it can be concluded that with decreasing diameter of piston up to 60 cc can reduce exhaust emissions, especially CO, HC and fuel consumption. The highest HC exhaust emissions was in 100 cc cylinder volume that is equal to 514.33 ppm while the lowest HC emissions obtained in 60 cc cylinder volume at 49.67 ppm. The highest CO emission was obtained on 100 cc cylinder by 4.64% volume, while the lowest CO emission was obtained on 60 cc cylinder by 0.31% volume. The highest CO2 emissions obtained in 60 cc cylinder amounted to 17.60% volume, while the lowest CO2 emission obtained at 100 cc cylinder amounted to 8.37% volume, and the highest fuel consumption obtained in 100 cc cylinder at 0.65 kg/h, and the lowest fuel consumption obtained in 60 cc cylinder by 0.06 kg/h.